The Bitter Side of Tourism: Political Ecology of Port Ownership Dispute and Identity Politics in Nusa Penida, Bali - Nyoman Ayu Sukma Pramestisari (Universitas Warmadewa, 2026)
Tourism expansion has increasingly become a dominant development strategy in many coastal and island regions of Indonesia. While tourism-led development is often associated with economic growth and infrastructure improvement, recent studies highlight its socio-ecological consequences, particularly the emergence of resource conflicts and uneven distribution of benefits. However, existing studies largely focus on vertical conflicts between local communities, investors, and the state, while limited attention has been given to the ways tourism development can generate horizontal conflicts among local communities themselves. This article addresses this gap by examining the ownership dispute over Nyuh Kukuh Port in Nusa Penida, Bali. This research employs a qualitative case study approach to investigate how tourism-driven economic transformation reshapes local resource relations and triggers inter-community conflict. Data were collected through in-depth interviews, field observations, and document analysis involving community members, local leaders, and relevant stakeholders. The findings show that the rapid growth of tourism since the early 2010s has transformed coastal livelihoods from seaweed farming and fisheries toward tourism-related services. The increasing economic value of port infrastructure generated new forms of competition over access and control of coastal resources. Unequal distribution of financial contributions from tourism transportation operators intensified tensions between Ped Village and Kampung Toya Pakeh Village, leading to competing claims over port ownership. The dispute further evolved through identity mobilization and local elite contestation. This study contributes to political ecology scholarship by demonstrating how tourism development can reconfigure local power relations and transform environmental resource disputes into horizontal conflicts mediated by identity politics.